Maxi J1820+070 with Nustar I. An increase in variability frequency but a stable reflection spectrum: Coronal properties and implications for the inner disc in black hole binaries - Buisson, D. J. K.; Fabian, A. C.; Barret, Didier; Furst, F.; Gandhi, P.; Garcia, Javier; Kara, E.; Madsen, K. K.; Miller, J. M.; Parker, M. L.; Shaw, A. W.; Tomsick, J. A.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
MAXI J1820+070 (optical counterpart ASASSN-18ey) is a black hole candidate discovered through its recent very bright outburst. The low extinction column and long duration at high flux allow detailed measurements of the accretion process to be made. In this work, we compare the evolution of X-ray spectral and timing properties through the initial hard state of the outburst. We show that the inner accretion disc, as measured by relativistic reflection, remains steady throughout this period of the outburst. Nevertheless, subtle spectral variability is observed, which is well explained by a change in coronal geometry. However, characteristic features of the temporal variability – low-frequency roll-over and quasi-periodic oscillation frequency – increase drastically in frequency, as the outburst proceeds. This suggests that the variability time-scales are governed by coronal conditions rather than solely by the inner disc radius. We also find a strong correlation between X-ray luminosity and coronal temperature. This can be explained by electron pair production with a changing effective radius and a non-thermal electron fraction of ∼ 20 per cent.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Accretion accretion discs; Black hole physics; X-rays: binaries